2015
DOI: 10.1371/journal.pone.0139156
|View full text |Cite
|
Sign up to set email alerts
|

Relative Deprivation and Relative Wealth Enhances Anti-Immigrant Sentiments: The V-Curve Re-Examined

Abstract: Previous research has shown that negative attitudes towards immigrants and support for anti-immigrant parties are observed both among those experiencing relative deprivation and those experiencing relative gratification (so called v-curve). Whereas the effect of relative deprivation is intuitive, the effect of relative gratification is more difficult to explain. Why would economic prosperity provoke negative attitudes towards immigrants? We first present correlational (Study 1) and experimental (Study 2) suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
169
1
8

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 149 publications
(186 citation statements)
references
References 54 publications
8
169
1
8
Order By: Relevance
“…Participants were then asked to imagine that they were going to live in a fictitious society called Bimboola (Jetten, Mols, & Postmes, 2015). Participants learned that Bimboola consisted of three income groups, and all participants were assigned to the middle-income group, which earned 7,000 Bimbolean Coins (BC) per month.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were then asked to imagine that they were going to live in a fictitious society called Bimboola (Jetten, Mols, & Postmes, 2015). Participants learned that Bimboola consisted of three income groups, and all participants were assigned to the middle-income group, which earned 7,000 Bimbolean Coins (BC) per month.…”
Section: Methodsmentioning
confidence: 99%
“…The notion that opposition to immigration may not be linearly related to declining wealth has inspired vcurve research which proposes that both relative deprivation and relative gratification may underlie prejudice and negative attitudes towards minorities (Dambrun et al, 2006;Grofman & Muller, 1973;Guimond & Dambrun, 2002;Jetten et al, 2015;Moscatelli et al, 2014;Postmes & Smith, 2009). 2 Specifically, among a large representative sample in South Africa, Dambrun et al (2006) found that hostility towards immigrants was associated with participants' perceptions of economic deprivation (i.e., that they were dissatisfied with their personal economic conditions) and with perceptions of economic gratification (i.e., satisfaction with their own personal economic conditions), resulting in a v-curve relationship.…”
Section: For Whom Will Attitudes Towards Minoritiesmentioning
confidence: 99%
“…To further explore relative deprivation and relative gratification processes, we developed an experimental paradigm with the aim to make participants temporarily feel wealthy or poor (for details, see Jetten et al, 2015). Participants in the study were introduced to a hypothetical society called Bimboola after which they were told that, just like any other society, there are wealthy and poor groups in Bimboola.…”
Section: For Whom Will Attitudes Towards Minoritiesmentioning
confidence: 99%
“…Study 5 was similar to Study 3. Participants’ perceived social class was manipulated by the same virtual society paradigm (Jetten et al., ) used in Study 3. After the manipulation, participants completed the manipulation check ( α = .99) and the same scales as used in Study 3 measuring desire for wealth and status ( α = .83 and .89, respectively).…”
Section: Studymentioning
confidence: 99%